Des Triple Algorithm in Security Office Data Security Mayor Pematangsiantar: Des Triple Algorithm in Security Office Data Security Mayor Pematangsiantar - Juli Wahyuni; Indra Gunawan; Ika Okta Kirana; Rafiqa Dewi; Solikhun Solikhun (Institute of Computer Science (IOCS), 2020)
In this era, technology is increasingly advanced and rapid, where data confidentiality is one of the things that is very important for a company. Employee data is data that is very important for the company. So it needs a system that can secure a database of employees from various types of hecker attacks or eavesdroppers who can steal and damage data. Cryptography is a science based on mathematical techniques that deal with information security such as data confidentiality. Triple DES algorithm is a development of DES algorithm, the algorithm used is the same, only in Triple DES algorithm, the encryption and decryption process is done 3 times. Triple DES also has three different keys. The three keys used can be mutually independent (K1 ? K2 ? K3) or only two keys are mutually independent and one other key is the same as the first key (K1 ? K2 and K3 = K1). This algorithm can generate encryption that cannot be read or understood by humans and results in the exact decryption of the initial plaintext input.